2009
DOI: 10.1111/j.1600-048x.2008.04650.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that plumage bacteria influence feather coloration and body condition of eastern bluebirdsSialia sialis

Abstract: Parasites influence the expression of secondary sexual traits and the health of infected individuals. We set out to test the influence of reputed exogenous parasites, plumage bacteria, including feather‐degrading bacteria (FDB), on secondary sexual characteristics and body condition of wild adult eastern bluebirds Sialia sialis. Previous work has shown that FDB alter the coloration of structurally‐colored bluebird feathers in vitro (Shawkey et al. 2007). In a correlational study of how bacteria affect birds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 58 publications
1
75
0
3
Order By: Relevance
“…Shawkey et al (2007) found a positive correlation between the brightness of male eastern bluebirds' (Sialia sialis) structural feather colouration and bacterial loads on their feathers. In contrast, carotenoid-based plumage colouration in house finches (Carpodacus mexicanus) and plumage brightness in female bluebirds were found to be negatively correlated to the densities of feather-degrading bacteria (Shawkey et al 2009;Gunderson et al 2009). Feather colour saturation was also found to be negatively correlated to the number of bacterial species on female great tit feathers (Kilgas et al 2012a).…”
mentioning
confidence: 83%
“…Shawkey et al (2007) found a positive correlation between the brightness of male eastern bluebirds' (Sialia sialis) structural feather colouration and bacterial loads on their feathers. In contrast, carotenoid-based plumage colouration in house finches (Carpodacus mexicanus) and plumage brightness in female bluebirds were found to be negatively correlated to the densities of feather-degrading bacteria (Shawkey et al 2009;Gunderson et al 2009). Feather colour saturation was also found to be negatively correlated to the number of bacterial species on female great tit feathers (Kilgas et al 2012a).…”
mentioning
confidence: 83%
“…Feather-degrading bacilli occur in the plumage of all avian species sampled to date [4,21]. Furthermore, in the only field study, Gunderson et al [22] showed that feather-degrading bacilli were active in the plumage of eastern bluebirds (Sialia sialis) and altered feather colour, reduced body condition and lowered reproductive success. We assume that feather-degrading bacilli are present in the plumage of parrots and that their presence has potential consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The plumage ecosystem is a nutrient-poor, dry environment, which raises questions about colonization by new microbes as the bird migrates. However, Gunderson et al [10] have shown that featherdegrading bacilli actively degrade feather keratin and change the spectral reflectance of the feathers in Eastern Bluebirds (Sialia sialis) during the breeding season. Taken together, these studies strongly suggest that the microbial community is a dynamic, functioning ecosystem open to the influence of local habitats.…”
Section: Introductionmentioning
confidence: 99%